2018
DOI: 10.1007/s00592-018-1136-9
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between serum apolipoproteins levels and retinopathy risk in subjects with type 2 diabetes mellitus

Abstract: Elevated level of apoAI might be a protective factor for diabetic retinopathy. Increased levels of apoCIII, apoE, apoCIII-to-apoAI and apoE-to-apoAI ratios might be risk factors for this complication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 32 publications
0
27
1
Order By: Relevance
“…Elevated ApoA1 levels could be a protective factor against DR, where a baseline serum level of ApoAI ≥ 7.4 lmol/L was associated with a decreased risk of DR. In contrast, baseline levels of ApoCIII ≥ 6.3 lmol/L and ApoCIIIto-ApoAI ratio ≥0.9 correlated with an increased risk of DR (Zhang et al, 2018). Further studies by Chung et al and Moosaie et al also report an inverse relationship between ApoA1 and DR severity and a positive correlation of ApoB/ApoAI ratio to DR severity (Chung et al, 2019;Moosaie et al, 2020).…”
Section: Enzyme Inhibitorsmentioning
confidence: 89%
See 2 more Smart Citations
“…Elevated ApoA1 levels could be a protective factor against DR, where a baseline serum level of ApoAI ≥ 7.4 lmol/L was associated with a decreased risk of DR. In contrast, baseline levels of ApoCIII ≥ 6.3 lmol/L and ApoCIIIto-ApoAI ratio ≥0.9 correlated with an increased risk of DR (Zhang et al, 2018). Further studies by Chung et al and Moosaie et al also report an inverse relationship between ApoA1 and DR severity and a positive correlation of ApoB/ApoAI ratio to DR severity (Chung et al, 2019;Moosaie et al, 2020).…”
Section: Enzyme Inhibitorsmentioning
confidence: 89%
“…By contrast, circulating ApoAI levels are inversely associated with DR, according to severity, in several studies of people with diabetes (Sasongko et al, 2011;Hu et al, 2012;Moosaie et al, 2020). A recent study by Zhang et al, (2018) further confirmed the association between circulating ApoAI and risk of DR but also found a positive relationship for ApoCIII levels. Elevated ApoA1 levels could be a protective factor against DR, where a baseline serum level of ApoAI ≥ 7.4 lmol/L was associated with a decreased risk of DR.…”
Section: Enzyme Inhibitorsmentioning
confidence: 91%
See 1 more Smart Citation
“…With in-depth investigations, the serum levels of traditional lipid profiles slightly increased, but the apolipoproteins collectively improved the area by approximately 8%. A combination of traditional lipid profiles and apolipoproteins showed improvement by more than 7% [72].…”
Section: Apolipoproteinsmentioning
confidence: 99%
“…The final glycation products that accumulate in hyperglycemia play an important role in the DR pathogenesis [8]. On the other hand, elevated levels of apoCIII and apoE lipoproteins are also the risk factors for DR [9]. Presence of hypertension is also important [10].…”
Section: The Main Causes Of Sight Lossmentioning
confidence: 99%